Floods – a permanent threat to building structures on the example of the Odra River basin - Dobrzeniecki, Mariusz; Bajno, Dariusz; Szer, Jacek (Archives of Civil Engineering, 2026)
The article is a summary of the authors’ experiences, who participated in examination and assessment of damage caused by floods to building structures, particularly in the recent period, i.e., in September 2024. The primary goal the authors set was to present the scale of the problem of damage that has been caused by floods, as well as their subsequent consequences. The article also references experiences gained during earlier disasters of similar or even greater magnitude that occurred at the end of the 20th century and in the first decades of the 21st century. Floodwaters pose both structural and microbiological threats to buildings and structures, but they are also a threat to the mental well-being of their occupants and of those providing assistance to the flood victims. The mental state of the specialists assessing the extent of the damage had a significant impact on the quality of those evaluations; therefore, could not be omitted in the assessment of the technical condition of the damaged structures. The impact of floodwaters on the nature of degradation and the durability of building materials is also not yet fully understood. The article, using selected examples from the authors’ own work [1–3] and literature sources [4–6], presents the issue of flood-related damage mainly over the past thirty years. It discusses methods of handling structures that have been in contact with floodwaters and also summarizes the effectiveness of the emergency and repair measures implemented for them. As part of the technical condition assessment, the moisture content of building partitions in residential structures was also examined selectively, along with an evaluation of their salt content. The results obtained were compared with permissible values, as well as with corresponding partitions in buildings of a similar structural state that had not been exposed to floodwaters.